Hubungan Media Sosial Melalui Konser Musik #dirumahaja Terhadap Pembentukan Citra Narasi TV - Syeri Kurnia Ramadhita; Vinda Fauzia Hamdani Putri; Ajeng Setia Utari (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2021)
ABSTRACT Since WHO declared the case of corona or covid-19 as a global pandemic, many activities outside the home have been postponed or carried out remotely. Indonesia enforces a Work From Home or WFH policy to minimize the spread of the virus. This has had an impact on Indonesian musicians as well, resulting in them being unable to take the stage off air during this global pandemic to avoid the spread of this virus. Najwa Shihab, co-founder of Narasi TV, held a charity concert entitled